Decree No. 643 of the year 2013 dated 12/12/2013 regarding the maximum limits of permissible disparity in Weights, Measures, and gauges in case of inspection and hallmarking / Egypt. Ministry of supply ; translated by The middle east library for economic services. - Egypt. Ministry of supply; The middle east library for economic services, translator. (2025)
Serial No. 67/2013